A review on the current state of the art for the production of advanced liquid biofuels - Fivga, Antzela; Speranza, Lais Galileu; Branco, Carolina Musse [UNESP]; Ouadi, Miloud; Hornung, Andreas (American Institute of Mathematical Sciences (AIMS), 2019)
Recent socio-political and economic factors encourage development of bioenergy and biofuels. The aim of this paper is to provide an updated review of the most promising technologies for sustainable production of advanced liquid biofuels, specifically transportation fuels. The focus is on second generation biofuels since they do not compete with land required for arable and pastoral use; therefore, first generation biofuels are not included in this review. Upon evaluation the authors recognise the most promising liquid biofuels to include bioethanol, biobutanol, biodiesel, green diesel, biomethanol, dimethyl ether, bio-oil, and biojet fuel. The order of the paper follows a specific structure. Initially, a detailed description, including physical and chemical properties, is given for each liquid biofuel. Then a review of production pathways for each fuel is given, including details regarding the feasibility of integrating it into the current liquid fuel infrastructure. Furthermore, a discussion of the challenges associated with current production pathways is provided.
Keywords: Bio-oil; Biodiesel; Bioenegy; Biofuels; Biomass; Second generation